2010
DOI: 10.3340/jkns.2010.48.1.20
|View full text |Cite
|
Sign up to set email alerts
|

GRIM-19 Expression and Function in Human Gliomas

Abstract: Objective :We determined whether the expression of GRIM-19 is correlated with pathologic types and malignant grades in gliomas, and determined the function of GRIM-19 in human gliomas. Methods : Tumor tissues were isolated and frozen at -80˚C just after surgery. The tissues consisted of normal brain tissue (4), astrocytomas (2), anaplastic astrocytomas (2), oligodendrogliomas (13), anaplastic oligodendrogliomas (11), and glioblastomas (16). To profile tumor-related genes, we applied RNA differential display us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The GeneFishing technique allows the detection of genes differentially expressed between two or more RNA samples and has been used extensively to isolate genes related to cancer, apoptosis, and immune responses Jin et al, 2010). We demonstrated that this technology can also be applied to insect systems; using this technology, we identified βGRP and attacinlike, alcohol-dehydrogenase-like, lipid-transport-like, 3oxoacyl-synthase-like, esterase-like, and ribosomal-like genes in the beet armyworm, a major pest species.…”
Section: Discussionmentioning
confidence: 99%
“…The GeneFishing technique allows the detection of genes differentially expressed between two or more RNA samples and has been used extensively to isolate genes related to cancer, apoptosis, and immune responses Jin et al, 2010). We demonstrated that this technology can also be applied to insect systems; using this technology, we identified βGRP and attacinlike, alcohol-dehydrogenase-like, lipid-transport-like, 3oxoacyl-synthase-like, esterase-like, and ribosomal-like genes in the beet armyworm, a major pest species.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, GRIM-19 encodes a 16-kDa protein of 144 amino acids [9]. The GRIM-19 protein contains no conserved domain structures and motifs.…”
Section: Introductionmentioning
confidence: 99%